Artemis Fowl - Colfer, Eoin.; Parker, Nathaniel (New York, N.Y. : Listtening Library, 2004)
When a twelve-year-old evil genius tries to restore his family fortune by capturing a fairy and demanding a ransom in gold, the fairies fight back with magic, technology, and a particularly nasty troll.
aUnabridged.
Read by Nathaniel Parker.
Keywords: Children's audiobooks; Fairies -- Fiction; Kidnapping -- Fiction; Magic -- Fiction; Mothers and sons -- Fiction; Audiobooks; England -- Fiction